Peripheral Frequency of CD4+ CD28− Cells in Acute Ischemic Stroke. Issue 20 (May 2015) - Tuttolomondo, Antonino; Pecoraro, Rosaria; Casuccio, Alessandra; Di Raimondo, Domenico; Buttà, Carmelo; Clemente, Giuseppe; Corte, Vittoriano della; Guggino, Giuliana; Arnao, Valentina; Maida, Carlo; Simonetta, Irene; Maugeri, Rosario; et al.
<x xml:space="preserve">Abstract</x> Abstract CD4+ CD28− T cells also called CD28 null cells have been reported as increased in the clinical setting of acute coronary syndrome. Only 2 studies previously analyzed peripheral frequency of CD28 null cells in subjects with acute ischemic stroke but, to our knowledge, peripheral frequency of CD28 null cells in each TOAST subtype of ischemic stroke has never been evaluated. We hypothesized that CD4+ cells and, in particular, the CD28 null cell subset could show a different degree of peripheral percentage in subjects with acute ischemic stroke in relation to clinical subtype and severity of ischemic stroke. The aim of our study was to analyze peripheral frequency of CD28 null cells in subjects with acute ischemic stroke in relation to TOAST diagnostic subtype, and to evaluate their relationship with scores of clinical severity of acute ischemic stroke, and their predictive role in the diagnosis of acute ischemic stroke and diagnostic subtype We enrolled 98 consecutive subjects admitted to our recruitment wards with a diagnosis of ischemic stroke. As controls we enrolled 66 hospitalized patients without a diagnosis of acute ischemic stroke. Peripheral frequency of CD4+ and CD28 null cells has been evaluated with a FACS Calibur flow cytometer. Subjects with acute ischemic stroke had a significantly higher peripheral frequency of CD4+ cells and CD28 null cells compared to control subjects without acute ischemic stroke. Subjects with cardioembolic stroke had a significantly higher peripheral frequency of CD4+ cells and CD28 null cells compared to subjects with other TOAST subtypes. We observed a significant relationship between CD28 null cells peripheral percentage and Scandinavian Stroke Scale and NIHSS scores. ROC curve analysis showed that CD28 null cell percentage may be useful to differentiate between stroke subtypes. These findings seem suggest a possible role for a T-cell component also in acute ischemic stroke clinical setting showing a different peripheral frequency of CD28 null cells in relation of each TOAST subtype of stroke.